1995
DOI: 10.1136/jcp.48.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality assurance in a clinical virology laboratory. I. Internal quality assessment.

Abstract: An internal quality assessment scheme (IQAS) can be used to monitor the quality of work more frequently and reproduce normal test conditions more accurately that NEQAS. IQAS samples can be provided in sufficient numbers and should not be more vigorously tested that any other routine specimen.In the IQAS some specimens received in the laboratory are resubmitted for testing anonymously, thus all activities involved in the passage of specimens through the laboratory starting from reception and ending in the dispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Quality assurance procedures include quality assessments (external or internal), quality controls (QC) (negative, positive, internal controls), equipment monitoring, and audits. [3][4][5] There are various methods for monitoring QC values which may aid in the evaluation of uncertainty of test results. The type of evaluation done will depend on whether the test provides a quantitative or qualitative result.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assurance procedures include quality assessments (external or internal), quality controls (QC) (negative, positive, internal controls), equipment monitoring, and audits. [3][4][5] There are various methods for monitoring QC values which may aid in the evaluation of uncertainty of test results. The type of evaluation done will depend on whether the test provides a quantitative or qualitative result.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this type of procedures is recognized by reference organizations such as the Eurachem and the Standard Unit, Microbiology Services of Public Health England, which recommend them to assess internally the overall reproducibility of samples testing and handling [29,30]. However, there is very few original publications in clinical microbiology setting supporting these recommendations, the only ones being the studies conducted in Cambridge in the nineties by Constantine et al [31] and Gray et al [32]. The authors concluded then that their works showed the capacity of this system to detect error, highlighted point of improvements and produced relevant data on the reproducibility of their results and the overall quality of their laboratories [31][32][33].…”
Section: Introductionmentioning
confidence: 99%